Swift’s Irish Writings
XXVI, 281 p.
Keywords: This edition presents Jonathan Swift's most important Irish writings in both prose and verse, together with an introduction, head notes and annotations that shed new light on the full context and significance of each piece. Familiar works such as "Gulliver's Travels" and "A Tale of a Tub" acquire new and deeper meanings when considered within the Irish frameworks presented in the edition. Differing in noteworthy ways from the more traditional, canonical, Anglocentric picture conveyed by other published volumes, the Swift that emerges from these pages is a brilliant polemicist, popular satirist, political agitator, playful versifier, tormented Jeremiah, and Irish patriot.